Application of Cooperative Learning Learning by Utilizing Smart TV Media in Libraries to Increase Motivation to Study ICT / Informatics Subjects in Class XI MIPA 4 SMAN 1 Brebes Odd Semester 2022 - A.Iwan Sri Harto (PT FORMOSA CENDEKIA GLOBAL, 2023)
ICT/Informatics subject learning in MIPA classes in high schools needs to be carried out using effective methods so as to increase students' ability to understand information and communication technology. One of them is the Cooperative Learning Learning Method. This study aims to see the effect of cooperative learning through literature study and group work on increasing motivation to learn in the subject of ICT/Informatics in class XI MIPA 4 students at SMA Negeri 1 Brebes, as well as looking at students' activities during the learning process. This study used a class action research method which was taken in two cycles. Each cycle has four stages, namely planning, implementing, observing and reflecting. It can be concluded that the Cooperative Learning method can increase the motivation and activity of students in class, seen from the increase in students' understanding of Information and Communication Technology and students' interest in developing it.